Factors associated with self-medication in users of drugstores and pharmacies in Peru: An analysis of the national survey on user satisfaction of health services, ENSUSALUD 2015 - Urrunaga-Pastor, Diego (2020)
Background: Irresponsible self-medication is a problem for health systems in developing countries. We aimed to estimate the frequency of self-medication and associated factors in users of drugstores and pharmacies in Peru. Methods: We performed a secondary data analysis of the 2015 National Survey on User Satisfaction of Health Services (ENSUSALUD), a two-stage probabilistic sample of all regions of Peru. Non self-medication (NSM), responsible self-medication (RSM) and irresponsible self-medication (ISM) were defined as the outcome categories. Demographic, social, cultural and health system variables were included as covariates. We calculated relative prevalence ratios (RPR) with their 95% confidence intervals (95%CI) using crude and adjusted multinomial logistic regression models for complex samples with NSM as the referent category. Results: 2582 participants were included. The average age was 41.4 years and the frequencies of NSM, RSM and ISM were 25.2%, 23.8% and 51.0%; respectively. The factors associated with RSM were male gender (RPR: 1.35; 95%CI: 1.06-1.72), being between 40 and 59 years old (RPR: 0.53; 95%IC: 0.39-0.72), being 60 or older (RPR: 0.39; 95%IC: 0.25-0.59), not having health insurance (RPR: 1.89; 95%CI: 1.31-2.71) and living in the Highlands region (RPR: 2.27; 95%CI: 1.23-4.21). The factors associated with ISM were male gender (RPR: 1.41; 95%CI: 1.16-1.72), being between 40 and 59 years old (RPR: 0.68; 95%IC: 0.53-0.88), being 60 or older (RPR: 0.65; 95%IC: 0.48-0.88) and not having health insurance (RPR: 2.03; 95%CI: 1.46-2.83). Conclusion: Around half of the population practiced ISM, which was associated with demographic and health system factors. These outcomes are the preliminary evidence that could contribute to the development of health policies in Peru.